2022
DOI: 10.1021/acs.jpcc.2c05261
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Reactivity of Graphene Driven by Mechanical Distortions

Abstract: In mechanochemistry, the application of controlled forces is key to altering reaction rates and pathways to direct product yields and selectivity. However, a fundamental knowledge gap exists between what is occurring on the atomic scale in mechanically driven reactions and the resulting macroscale outcomes. Two-dimensional (2D) materials, such as graphene, proffer a model system to study the impact of mechanical forces, such as strain, on chemical reactivity, as force distributions may be applied across a well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 73 publications
1
10
0
Order By: Relevance
“…Therefore, a ( Δ E Δ E BE ) value of 0.25 in Figure d corresponds to ≈0.10 eV of thermodynamic drive when the ΔE BE is ≈−0.40 eV. Hence, we conclude that the thermodynamic drive is substantial enough to observe the π–π NCI-driven migration for experimentally realizable curvatures and length scales. …”
mentioning
confidence: 69%
“…Therefore, a ( Δ E Δ E BE ) value of 0.25 in Figure d corresponds to ≈0.10 eV of thermodynamic drive when the ΔE BE is ≈−0.40 eV. Hence, we conclude that the thermodynamic drive is substantial enough to observe the π–π NCI-driven migration for experimentally realizable curvatures and length scales. …”
mentioning
confidence: 69%
“…This is in line with previous findings from our groups, showing that positive POAV angle regions (such as mountains) are more prone to out-of-plane functionalization and have stronger covalent binding with an adsorbate. 13,30 This is due to the fact that the functionalization of graphene C�C causes pyramidalization and out-of-plane distortion of the graphene C. 13,30 Therefore, regions that are closer to pyramidal geometry, that is, the regions with positive POAV angle, can offer a stronger binding.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Previous reports show that mechanical perturbations, such as strain and curvature of 2D materials, can be realized experimentally using state-of-the-art methods. The use of mechanical distortion provides an alternate avenue to perform chemical reactions apart from thermal, photochemical, or electrochemical approaches. Furthermore, mechanochemistry enables one to realize novel chemical processes and perform directed chemical syntheses on 2D materials. Recently, we have demonstrated that directional molecular motion can be attained on graphene by exploiting mechanical distortions .…”
Section: Introductionmentioning
confidence: 99%
“…Covalent bonds are observed near the entanglement, both between the two nanotubes and between the walls of multiwalled nanotubes. These bonds form at the most extreme curvature areas at the edges of buckles due to the increased reactivity from the mechanical distortion. The number of sp 3 hybridized carbons varies between models and over the duration of the loading simulation within a model but can range up to several hundred in a single entanglement. For example, the model shown in Figure a contains 48 sp 3 hybridized carbon atoms and the model shown in Figure c contains 141 sp 3 hybridized carbon atoms at the beginning of the loading simulation.…”
Section: Resultsmentioning
confidence: 99%